Effectivity of Piezoelectric Transition Elements in Modelling of Electro-Mechanical Systems (Agricultural Engineering, 2019)
The paper analyzes the development opportunities of solar systems in the Republic of Serbia. Renewable energy sources and their energy potential, such as solar energy, should be considered in order to meet the needs of consumers. Solar energy can be considered the most modern renewable energy whose utility is still developing, and it is not represented as the utilization of hydro energy sources. Researches show that Serbia is a country with a high RES potential and that it has favorable conditions for production of electrical and heat energy from renewable sources. The aim of this paper is to present the possibilities of using solar energy in Serbia. Energy supply from renewable energy sources is a key factor for each country's strategy, because it directly contributes to reducing the negative effect on the environment.